ANALISA PENGARUH FAKTOR- FAKTOR MAKROEKONOMI DAN KEBIJAKAN KEUANGAN TERHADAP TINGKAT PENYALURAN KREDIT PERUMAHAN DI INDONESIA - Meliza SE.M.Com; Danang Satrio (Fakultas Ekonomi Universitas Pekalongan, 2015)
The increasing of housing needs in Indonesia result in the increasing of housing demand. However, bothgoverment and private sectors still can not provide affordable house. One of goverment policy toincerease the purchasing power of housing is by generates subsidizies fund for housing loan called“Fasilitas Likuiditas Pembiayaan Perumahan”. This fund aims to create affordable housing loan.Furthermore, banking sector which has important role in distribution of housing fund faces someproblems to raise the housing loan distribution. This condition caused by some macroecomonic factorssuch as the rate of inflation and fluctuation of Indonesia exchange rate called “rupiah”. Moreover,interest rates as one of government financial policies also influence the level of housing loan. Therefore,this research purposes to analyze both macroeconomics and financial policy factors that affect the levelof housing loan distribution. Besides, this research also uses multiple regressions and multiplecorrelations to analysis the influence of macroeconomics and financial policy factors. The multipleregressions and multiple correlations show that interest rate, inflation rate, and fluctuation of exchangerate have influence to the housing loan level of distribution. The interest rate has significant influenceand correlation to the housing loan level distribution. Nevertheless, the fluctuation of Indonesiaexchange rate has low correlation and influence to the housing loan level of distribution. Keywords : kredit perumahan, tingkat penyaluran kredit